Academic Leadership of School Administrators Under Kanchanaburi Primary Educational Service Area Office 4 - Thongsrimuang, Phakamat; Pumklom, Mitparnee; Ruamchomrat, Pongsak (Journal of Faculty of Humanities and Social Sciences Thepsatri Rajabhat University, 2023)
The purposes of this research were to study and compare the academic leadership of school administrators under Kanchanaburi Primary Educational Service Area Office 4. The samples consisted of 234 teachers in primary schools under Kanchanaburi Primary Educational Service Area Office 4, selected by proportionate stratified random sampling. The research instrument was a 5 -leval rating scale questionnaire with reliability at 0.94. The data were analyzed using percentage, mean, standard deviation, one-way analysis of variance and a pair wise difference by mean of Scheffe’s. The research findings were as follows: 1. The academic leadership of school administers in primary schools under Kanchanaburi Primary Educational Service Area Office 4, in all and each aspect were at a high level, ranking from the aspect of promoting academic atmosphere, following of supervision, planning and management. And 2. The academic leadership of school administers under Kanchanaburi Primary Educational Service Area Office 4, classified by educational management areas, in all aspects were not different statistically significant difference at 0.05 level, when each aspect was considered, it was found that the planning aspect was significantly different at the 0.05 level.